MEMBENTUK JIWA SOSIAL YANG PEDULI TERHADAP LINGKUNGAN DAN MENINGKATKAN PENGETAHUAN SERTA KREAKTIVITAS DALAM MENYELESAIKAN MASALAH DI MASYARAKAT - Vinsensius S. Buulolo; Benekdiktus H. Buulolo; Depiaman Gea; Desilina Bago; Eka Putra Laia; Filifo Giawa; Newiman Halaman; Pansakti Laia; Polikar Laowo; Yastina Laowo; Tobias Duha (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
The development of a social spirit that emphasizes environmental awareness, carried out by the Community Service Program (KKN) students of Universitas Nias Raya, plays a significant role in enhancing knowledge and understanding of the importance of maintaining a clean and orderly environment in Samiri Village. The purpose of this study is to provide a comprehensive understanding and to encourage community participation in environmental preservation. In this regard, the cultivation of social concern enables the residents of Samiri Village not only to recognize local environmental issues but also to generate creative and innovative solutions. Therefore, it is essential for the KKN students of Universitas Nias Raya to maintain continuous collaboration with the community of Samiri Village in integrating values of environmental awareness and promoting sustainable practices for a clean and healthy environment.